Current status of hematopoietic stem cell transplantation in Russia - L. P. Mendeleeva; V. G. Savchenko; L. S. Lubimova; I. A. Demidova; B. V. Afanassiev; L. S. Zubarovskaya; T. P. Zagoskina; I. S. Zuzgin; T. S. Konstantinova; V. A. Lapin; I. A. Lisukov; A. B. Loginov; et al. (Онкогематология, 2022)
Russian Interregional Register of hematopoietic stem cell transplantation was established in 2000. 11 transplant centres from 7 Russian cities are including in Register now. In this analysis we applied transplant activity survey data from 01.01.1996 to 31.12.2006. A total 1118 transplants (846 – autologous and 272 – allogeneic) were carried during this period.